A contribuição da sistematização de experiências para o fortalecimento do campo agroecológico e da agricultura familiar no Brasil - Sanches, Cinara Del'Arco (Universidade Federal de São Carlos, 2011)
Despite all the advances, Brazil remains under the governmental politics orientation. This framework strengthens the support to agribusiness and agroindustrial sector, which leads to exportation, especially the agrochemicals dependent crops. This has contributed for the increase of the land concentration and the extension of agricultural borders. In this context the Agroecology emerges as a scientific proposal and delineates a set of actions and strategies that especially base the new paradigm of agricultural development demanded for familiar agriculture. The confrontation of the hegemonic model of production and consumption takes place in a playing field in society, which is primarily political. The increase of the agroecological experiences allows greater visibility and forges the creation of a socio-political environment conducive to networks and increasing connectivity between the networks and alliances, that fulfill the role to interchange the experiences and to actively participate of public spaces of debate and construction on the agricultural development. From this perspective, the systematization of experiences can help addressing the challenges of today therefore representing a strategy. That strategy analyzes critically the experiences in course and allows the sharing of the learning extracted during the process. For its strategic character, the systematization has been gaining space among civil society organizations and social movements even though still timidly. This research intends to develop the understanding of the relevance of the systematization of experiences, especially those facilitated by civil society organizations to strengthen the agroecological field and familiar agriculture. To this end, it revises the concepts Agroecology, Familiar Agriculture and Systematization, then it composes a method and systemizes the experience in the Policulture in semi-arid region Project, describing the main learning generated during and after initiative.
Keywords: Agroecologia; Agricultura familiar; Sistematização de experiências; Desenvolvimento rural; Organizações não-governamentais; Políticas públicas; CIENCIAS AGRARIAS